PERTANGGUNGJAWABAN PIDANA NOTARIS DAN PARA PIHAK YANG MEMALSUKAN SURAT KETERANGAN OBYEK PEWARIS - Billy Adhi Pramarta; Rachmad Safa'at; Prija Djatmika (Universitas Negeri Malang, 2018)
This article described the elements of criminal acts against falsification of inheritance certificate, the responsibility of a notary and the one whose certificate of inheritance had been falsified by the others, and the legal consequences of a court decision on the land which certificate of inheritance had been falsified by the other. The method used normative juridical by using a legislative approach and conceptual approach. The results of the study showed that the element of criminal acts against forgery of inheritance certificate is the intention and intent to falsify, the act violates the provisions of the Notary Position Act (UUJN), and the notary didn’t an act outside his authority. The criminal responsibility of a notary carried out his place it is proven to have committed a violation. The regulation didn’t specifically regulate criminal sanctions against notaries who have been falsified letters due to fraud and errors committed by the complainants. The legal consequences of a certificate of inheritance forged by one of the parties made by a notary were null and void because it has removed one of the heirs and the letter would be cancelled if the postulating party can prove in court in court.DOI: http://dx.doi.org/10.17977/um019v3i12018p022